Development of porous fabric‐hydrogel composite membranes with enhanced ion permeability for microalgal cultivation in the ocean. Issue 5 (1st August 2019) - Kim, Jongmin Q.; Choi, Younghoon; Kim, Youngtae; Lee, Jin‐Kyun; Lee, Jin Hyun; Park, Hanwool; Lim, Sang‐Min; Lee, Choul‐Gyun; Lee, Dae Sung; Na, Yang‐Ho
ABSTRACT: This article presents a strategy to develop the porous fabric‐hydrogel composite membranes (PFHCMs) with high nitrate ion (NO3 −, a source of a main nutrient, nitrogen) permeability and sufficient mechanical strength required for microalgal cultivation in the ocean. The porous structure in the PFHCMs is generated by using three different types of porogens: water‐soluble macromolecules, surfactant micelles, and CaCO3 microparticles. Various PFHCMs, composed mainly of poly(hydroxyethyl methacrylate) hydrogels and cotton fabric, are prepared with varying the content of monomer, initiator, and crosslinker and the type and content of porogen. Their morphological, physical, and mechanical properties are characterized for variables. Among three porogens, the surfactant micelles with a large enough amount produce the optimal PFHCMs with NO3 − ion permeability coefficient (5.49 × 10 −8 m 2 min −1, approximately 5 and 20 times higher than those of the fabric‐hydrogel composite membranes, synthesized without any porogen in a previous work, and the commercial cellulose acetate membranes, respectively). Their mechanical strength (i.e., the ultimate stress is 9.37 MPa) is high enough for practical uses. Therefore, these PFHCMs are good candidate membranes in microalgal cultivation for biorefinery and other biomedical applications, including wound dressings. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48324. Abstract : Porous fabric‐hydrogel composite membranes (PFHCMs) with enhanced nitrite ion (NO3 − ) permeability are developed by using three porogens: water‐soluble macromolecules, surfactant micelles, and CaCO3 microparticles. The PFHCMs prepared with surfactant micelles exhibit the most regular, uniform, and interconnected microporous morphology and provide the higher NO3 − permeability coefficient than the fabric‐hydrogel composite membranes and commercial cellulose acetate membranes.